Method for producing composite particle

JP2025036272APending Publication Date: 2025-03-14KAO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024145915
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-30
Filing Date
2024-08-27
Publication Date
2025-03-14

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、重合開始基の導入時に溶媒を用いた従来の方法と同等又は同等以上のグラフト密度の複合粒子が得られ、製造時の取り扱い性に優れた製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025036272000001
    Figure 2025036272000001
  • Figure 2025036272000002
    Figure 2025036272000002
  • Figure 2025036272000003
    Figure 2025036272000003
Patent Text Reader

Abstract

To provide a producing method capable of obtaining composite particle with graft density same as that of the conventional method that uses a solvent a the time of introduction of a polymerization initiator, and excellent in handleability during production.SOLUTION: A method for producing composite particles having polymer graft chains, including the following steps, wherein a step 1 is carried out in a powder state. (Step 1) reacting inorganic particles with a silane compound having a polymerization initiator group other than a halosulfonyl group to bind the polymerization initiator group to the inorganic particles; (Step 2) carrying out graft polymerization of a monomer in the presence of the inorganic particles to which the polymerization initiator is bound.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing composite particles. [Background technology]

[0002] Conventionally, as a technique for bonding polymer chains to inorganic particles such as metal particles, for example, composite particles are known in which the surface of a core particle is coated with a polymer layer by radical polymerization in the presence of a core particle mixed with a coupling agent having a polymerizable reactive group, a monomer component, and a polymerization initiator (Patent Document 1). It is known that bonding an organic polymer chain to an inorganic particle can impart various functions to the particle, such as vibration damping and antibacterial properties (Patent Documents 2 and 3).

[0003] However, in the production of the composite particles described in Patent Documents 1 and 2, a large amount of solvent is used when introducing the polymerization initiating group, so that the amount of inorganic particles that can be treated per unit volume is small, and there is a problem that the production efficiency cannot be improved. Furthermore, when the amount of the solvent used is reduced, a highly viscous slurry is formed, which is difficult to handle. In contrast, when producing the composite particles described in Patent Document 3, the amount of solvent used when introducing the polymerization initiating groups is small, and the particles can be handled as a powder even after the introduction of the polymerization initiating groups. This is thought to have solved the above problem. However, when the present inventors examined the technology of Patent Document 3, they found that there was room for improvement, since the graft density of the polymer graft chains was unexpectedly low in the technology of Patent Document 3. A higher graft density of the polymer graft chains on the surface of the composite particle has the advantages of better dispersibility of the composite particle and the possibility of introducing a larger amount of functional molecules. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-120365 A [Patent Document 2] JP 2020-196877 A [Patent Document 3] JP 2010-018535 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention relates to providing a production method which can obtain composite particles having a graft density equivalent to that obtained by a conventional method using a solvent when introducing a polymerization initiating group, and which is excellent in handleability during production. [Means for solving the problem]

[0006] The present invention relates to the following [1] to

[11] . [1] A method for producing composite particles having polymer graft chains, comprising the following steps, in which step 1 is carried out in a powder state. (Step 1) A step of reacting inorganic particles with a silane compound having a polymerization initiating group other than a halosulfonyl group to bond the polymerization initiating group to the inorganic particles. (Step 2) A step of graft polymerizing a monomer in the presence of inorganic particles to which the polymerization initiation groups are bonded [2] Among the components used in step 1, the ratio of the total mass (B [g]) of liquid substances at 25°C and 1 atmosphere to the total surface area (A [m 2 ]) ratio ((A) / (B)[m 2 / g]) is 20 or more. [3] The method for producing a liquid composition according to the above item [1] or [2], wherein the ratio ((A') / (B)) of the total mass of inorganic particles (A'[g]) to the total mass of liquid substances (B[g]) at 25°C and 1 atmospheric pressure used in step 1 is 2 or more. [4] The method for producing the polymerizable composition according to any one of the above [1] to [3], further comprising a step of contacting inorganic particles having a polymerization initiation group bonded thereto with a monomer under living radical polymerization conditions. [5] The graft density of polymer chains on the surface of the composite particle is 0.001 chains / nm 2 More than 5 chains / nm2 The method for producing a semiconductor device according to any one of the above items [1] to [4], [6] The method according to any one of the above [1] to [5], wherein the amount of the silane compound having a polymerization initiating group other than a halosulfonyl group used is 0.1 parts by mass or more and 100 parts by mass or less relative to 100 parts by mass of inorganic particles. [7] The method according to any one of the above [1] to [6], wherein the polymerization initiating group is an α-haloacyl group, a haloalkyl group, or a haloalkylphenyl group. [8] The method according to any one of the above [1] to [7], further comprising using at least one selected from the group consisting of ethanol, dichloromethane, toluene, acetone, tetrahydrofuran, methanol, butanol and butyl cellosolve in step 1. [9] The method according to any one of the above [1] to [8], further comprising using a catalyst in step 1.

[10] A method for producing a resin composition, comprising a step of mixing the composite particles obtained by the production method according to any one of [1] to [9] above with a resin.

[11] A method for producing composite particles having polymer graft chains, comprising the steps of: (a) preparing a composite particle having a polymer graft chain; and (b) carrying out step 1 in a powder state. resin A resin composition comprising: (Step 1) A step of reacting inorganic particles with a silane compound having a polymerization initiating group other than a halosulfonyl group to bond the polymerization initiating group to the inorganic particles. (Step 2) A step of graft polymerizing a monomer in the presence of inorganic particles to which the polymerization initiation groups are bonded Effect of the Invention

[0007] According to the present invention, composite particles having a graft density equal to or higher than that of conventional methods using a solvent when introducing a polymerization initiating group can be obtained, and a production method excellent in handleability during production can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present inventors have focused on the type of silane coupling agent used when introducing a polymerization initiator group into inorganic particles. The silane coupling agent used in Patent Document 1, a compound having a halosulfonyl group, tends to generate radicals frequently, so it was presumed that the graft polymerization reaction proceeds too quickly, resulting in a decrease in graft density. Therefore, when various silane coupling agents other than the compound having a halosulfonyl group were examined, it was found that when using such a silane coupling agent to introduce a polymerization initiator group into inorganic particles, the amount of liquid components such as solvents was reduced as much as possible, which not only improved the handling during production, but also unexpectedly achieved a high graft density.

[0009] <Method for producing composite particles having polymer graft chains> The method for producing composite particles having polymer graft chains of the present invention includes the following steps, in which step 1 is carried out in a powder state. (Step 1) A step of reacting inorganic particles with a silane compound having a polymerization initiating group other than a halosulfonyl group to bond the polymerization initiating group to the inorganic particles. (Step 2) A step of graft polymerizing a monomer in the presence of inorganic particles to which the polymerization initiation groups are bonded

[0010] In the present invention, the term "powder" refers to a collection of particles, in which no liquid phase can be confirmed by visual observation, no caking occurs, and which has fluidity. Liquidity means that both of the following conditions are met: - Pass through a funnel (with a bottom outlet diameter of 5 mm) without resistance -The angle of repose can be measured

[0011] In the present invention, the angle of repose of powder or particles can be measured using a Powder Tester PT-R manufactured by Hosokawa Micron Corporation. In the present invention, the angle of repose of the particles immediately after the completion of step 1 is preferably within a range of 25 degrees or more and 65 degrees or less. Therefore, for example, if the angle of repose of the particles immediately after the completion of step 1 is within a range of 25 degrees or more and 65 degrees or less, it can be said that step 1 has been carried out in a powder state.

[0012] In the present invention, "liquid" refers to a state of fluidity in which the change in volume with respect to a change in pressure is sufficiently small, and the viscosity at 25°C and 1 atmospheric pressure is preferably 10,000 mPa s or less, more preferably 8,000 mPa s or less, and even more preferably 4,000 mPa s or less. The above viscosity is the value measured for 1 minute at a specified rotation speed and temperature of 25°C using a B-type viscometer with a rotor appropriate for the applicable measurement range.

[0013] [Composite particles] The composite particles in the present invention are inorganic particles having polymer graft chains bonded to the surfaces thereof.

[0014] [Inorganic particles] Examples of inorganic particles include metal-based particles such as metal oxides, metal oxide salts, metal hydroxides, and metal carbonates, as well as non-metal particles. For example, the inorganic particles are one or more selected from the group consisting of silica, alumina, titania, zirconia, ferrite, magnesia, silica-titania, silicon carbide, silicon nitride, activated carbon, carbon black, carbon nanofibers, carbon nanotubes, calcium carbonate, calcium oxide, barium sulfate, diatomaceous earth, bentonite, perlite, mica, and talc, more preferably one or more selected from the group consisting of silicon oxides such as silica, and silicates such as mica and talc, and even more preferably silica.

[0015] From the viewpoint of increasing the rate of reaction with a silane compound having a polymerization initiating group other than a halosulfonyl group, the inorganic particle surface may be treated by a known method to increase the amount of hydroxyl groups, amino groups, etc. on the inorganic particle surface. The shape of the particles is not particularly limited, and examples thereof include plate-like, granular, needle-like, fibrous, etc. In this specification, the term "particle" refers to a particle used in the production of a composite particle.

[0016] The size of the inorganic particles is not particularly limited, but from the viewpoint of improving the graft density of the polymer graft chains on the surface of the composite particles, the average particle size is preferably 1 nm or more, more preferably 3 nm or more, even more preferably 10 nm or more, still more preferably 50 nm or more, and even more preferably 100 nm or more, while it is preferably 100 μm or less, more preferably 10 μm or less, still more preferably 1 μm or less, still more preferably 500 nm or less, and even more preferably 300 nm or less.

[0017] The size of inorganic particles is measured by the Coulter counter method using a Multisizer 3 (manufactured by Beckman Coulter, Inc., using a 20 μm aperture tube).

[0018] [Polymer graft chain] Examples of the polymer graft chain include homopolymers or copolymers of styrene-based monomers, nitrile-based monomers, (meth)acrylic-based monomers, unsaturated olefins, conjugated diene-based monomers, etc. Preferred are one or more homopolymers or copolymers selected from the group consisting of acrylic acid, methacrylic acid, and derivatives thereof, more preferred are one or more homopolymers or copolymers selected from methacrylic acid and derivatives thereof, and even more preferred is polybutyl methacrylate.

[0019] The graft density of the polymer graft chains on the surface of the composite particle is preferably 0.001 chains / nm from the viewpoint of functional expression. 2 More preferably, 0.01 chains / nm 2 More preferably, 0.1 chains / nm 2 On the other hand, from the viewpoint of ease of grafting of polymer chains, it is preferable to set the number of chains to 5 / nm. 2 Less than or equal to 3 chains / nm, more preferably 2More preferably, 2 chains / nm 2 More preferably, 1 chain / nm or less 2 The graft density is measured by the method described in the Examples below.

[0020] The number average molecular weight of the polymer graft chains in the composite particles is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 15,000 or more, from the viewpoint of controlling the film thickness of the polymer graft chains. From the same viewpoint, the number average molecular weight is preferably 1,000,000 or less, more preferably 500,000 or less, and even more preferably 200,000 or less. The number average molecular weight of the polymer graft chains is measured by the method described in the Examples below.

[0021] The glass transition temperature (Tg) of the polymer graft chain in the composite particle is, from the viewpoint of expressing functionality, preferably -30°C or higher, more preferably -10°C or higher, and even more preferably 10°C or higher, and from the same viewpoint, is preferably 80°C or lower, more preferably 50°C or lower, and even more preferably 40°C or lower. The glass transition temperature (Tg) of the polymer graft chains in the composite particles can be controlled by the monomers, molecular weight, and molecular weight distribution used in the production of the composite particles. The glass transition temperature (Tg) is measured by the method described in the Examples below.

[0022] The film thickness of the polymer graft chain in the composite particle is preferably 1 nm or more, more preferably 3 nm or more, and even more preferably 5 nm or more from the viewpoint of functionality expression, and from the same viewpoint, is preferably 1 μm or less, more preferably 100 nm or less, and even more preferably 40 nm or less. The film thickness of the polymer graft chains is calculated by the method described in the Examples below.

[0023] [Silane Compound Having a Polymerization Initiating Group Other than a Halosulfonyl Group] In the present invention, the "polymerization initiating group other than a halosulfonyl group" includes an α-haloacyl group, a haloalkyl group, or a haloalkylphenyl group.

[0024] Specific examples of the α-haloacyl group include an α-bromoacyl group and an α-chloroacyl group, and the alkyl group constituting the haloacyl group preferably has 3 to 11 carbon atoms. Specific examples of the haloalkyl group include a bromoalkyl group and a chloroalkyl group, and the alkyl group constituting the haloalkyl group preferably has 3 to 11 carbon atoms. Specific examples of the haloalkylphenyl group include a bromoalkylphenyl group and a chloroalkylphenyl group, and the alkyl group constituting the haloalkylphenyl group preferably has 3 to 11 carbon atoms. As the "polymerization initiating group other than a halosulfonyl group", an α-bromoacyl group is preferred, from the viewpoint that the graft density can be increased by introducing such a polymerization initiating group onto the surface of the inorganic particles.

[0025] A silane compound having a polymerization initiating group other than a halosulfonyl group can be synthesized by reacting a "silane compound" with a "compound having a polymerization initiating group" by a known method.

[0026] For example, as described in Synthesis Example 1 below, a silane compound (APTMS-Br) having a bromoacyl group, which is a polymerization initiating group, can be synthesized by reacting 3-aminopropyltrimethoxysilane with 2-bromoisobutyl bromide.

[0027] Examples of the silane compound that can be used in the present invention include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(2-aminoethylamino)propyltrimethoxysilane, 3-(2-aminoethylamino)propyldimethoxysilane, 3-aminopropyldimethoxymethylsilane, [3-(6-aminohexylamino)propyl]trimethoxysilane, 3-aminopropyldiethoxymethylsilane, 3-(2-aminoethylamino)propyltriethoxysilane, trimethoxysilane, dimethoxy(methyl)silane, diethoxymethylsilane, triethoxysilane, tris(trimethylsilyloxy)silane, and the like.

[0028] Examples of the compound having the above-mentioned polymerization initiating group that can be used in the present invention include, in addition to 2-bromoisobutyl bromide, 2-chloroisobutyl chloride, 2-bromopropionyl bromide, 2-chloropropionyl chloride, 2-bromo-2-phenylacetyl bromide, 2-chloro-2-phenylacetyl chloride, 2-bromo-2-methylallyl propionate, 1-(2-bromo-2-methyl)propionate-5-hexene, and 2-bromoisobutyrate-10-undecenyl.

[0029] As the silane compound having a polymerization initiating group other than a halosulfonyl group, a commercial product available as a silane coupling agent in the field of the present invention can be used, such as 3-(trimethoxysilyl)propyl bromo-2-methylpropanoate.

[0030] [Method for producing composite particles] The composite particles can be obtained by bonding polymer graft chains to the particle surface. The method for bonding polymer graft chains to the particle surface is not particularly limited as long as it is a method capable of grafting polymer chains, but a grafting from method in which polymer graft chains are polymerized from polymerization initiation points on the particle surface is preferred.

[0031] The polymerization method is not particularly limited, and examples thereof include radical polymerization, anionic polymerization, cationic polymerization, etc. Among these, from the viewpoint of easy control of the molecular weight and molecular weight distribution of the polymer chain and from the viewpoint of easy grafting of various copolymers, living radical polymerization, living anionic polymerization, and living cationic polymerization are preferred, and from the viewpoint of application to a wide range of monomers, living radical polymerization is more preferred.

[0032] As the living radical polymerization method, an atom transfer radical polymerization method (ATRP method), a reversible addition-fragmentation chain transfer polymerization method (RAFT method), and a nitroxide-mediated living radical polymerization method (NMP method) can be used, and from the same viewpoint, the atom transfer radical polymerization method (ATRP method) is preferable.

[0033] More specifically, a method for producing composite particles includes, for example, a production embodiment including the following steps 1 and 2.

[0034] [Process 1] Step 1 is a step of reacting inorganic particles with a silane compound having a polymerization initiator group other than a halosulfonyl group to bond the polymerization initiator group to the inorganic particles. Specifically, inorganic particles, a silane compound having a polymerization initiator group other than a halosulfonyl group, and optionally a catalyst, a solvent, etc. are added and mixed. More preferably, when inorganic particles and a catalyst are used, a silane compound having a polymerization initiator group other than a halosulfonyl group and optionally a solvent are added to the mixture of inorganic particles and catalyst, and mixed uniformly. The reaction temperature during the reaction between the silane compound and the inorganic particles is preferably 25° C. to 250° C., more preferably 150° C. or lower, and further preferably 120° C. or lower.

[0035] The amount of the silane compound having a polymerization initiation group other than a halosulfonyl group to be used relative to 100 parts by mass of inorganic particles is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1.0 parts by mass or more, from the viewpoint of the surface modification efficiency of the inorganic particles, while it is preferably 100 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 40 parts by mass or less, from the viewpoint of suppressing the reaction between the silane compounds.

[0036] It is preferable to carry out the reaction between the silane compound and the inorganic particles in a powder state in step 1. This is because the amount of inorganic particles that can be treated per unit volume can be increased, and production efficiency can be improved. In order to carry out step 1 in a powder state, for example, the amount of a substance that is liquid at 25°C and 1 atmospheric pressure, such as a solvent, may be as small as possible.

[0037] In the present invention, the term "use the smallest possible amount of substances that are liquid at 25° C. and 1 atmospheric pressure" refers to the ratio of the total surface area of ​​inorganic particles (A [m 2 ]) ratio ((A) / (B)[m 2 / g) is 20 or higher.

[0038] Here, from the viewpoint of carrying out step 1 in a powder state and from the viewpoint of improving the graft density of the polymer graft chains on the surface of the composite particle, (A) / (B) [m 2 / g] is 20 or more, preferably 45 or more, more preferably 50 or more, and further preferably 70 or more. On the other hand, from the viewpoint of the surface modification efficiency of the inorganic particles, (A) / (B)[m 2 / g] is preferably 1,000 or less, more preferably 800 or less, even more preferably 700 or less, and still more preferably 500 or less. The total surface area of ​​the inorganic particles can be determined by the method described in the Examples below.

[0039] Among the components used in step 1, substances that are liquid at 25°C and 1 atmospheric pressure include solvents and catalysts used in the field of the present invention that are liquid at 25°C and 1 atmospheric pressure, and silane compounds having a polymerization initiating group other than a halosulfonyl group.

[0040] Examples of the solvent that can be used in step 1 include solvents containing an organic solvent and / or water, and more specifically, water can be included in addition to organic solvents such as ethanol, dichloromethane, toluene, acetone, tetrahydrofuran, methanol, butanol, and butyl cellosolve. Among these, from the viewpoint of improving the dispersibility of the silane coupling agent with the inorganic particles and improving the graft density of the polymer graft chain on the surface of the composite particles, a solvent containing an organic solvent is preferred, and specifically, a solvent containing ethanol, toluene, tetrahydrofuran, or methanol is preferred, a solvent containing ethanol, toluene, or tetrahydrofuran is more preferred, and a solvent containing ethanol is even more preferred.

[0041] The mass ratio of the organic solvent to the silane coupling agent is preferably 0.1 or more, more preferably 0.5 or more, even more preferably 1 or more, even more preferably 2 or more, relative to 1 part of the silane coupling agent, from the viewpoint of performing step 1 in a powder state and from the viewpoint of improving the graft density of the polymer graft chains on the surface of the composite particles. The mass ratio of the organic solvent to 1 part of the silane coupling agent is preferably 0.1 or more, more preferably 0.5 or more, even more preferably 1 or more, even more preferably 2 or more, and is preferably 10 or less, more preferably 8 or less, and more preferably 4 or less.

[0042] In addition, from the viewpoint of improving the reactivity of the silane coupling agent with the inorganic particles and increasing the graft density of the polymer graft chains on the surfaces of the composite particles, it is preferable that the solvent in step 1 contains water.

[0043] The mass ratio of water to silane coupling agent is preferably 0.01 or more, more preferably 0.05 or more, even more preferably 0.1 or more, even more preferably 0.2 or more, preferably 1 or less, more preferably 0.5 or less, and more preferably 0.3 or less, relative to 1 part of silane coupling agent, from the viewpoint of performing step 1 in a powder state and from the viewpoint of improving the graft density of the polymer graft chains on the surface of the composite particles.

[0044] When an organic solvent and water are used in combination, the mass ratio of the alcohol and water to the silane coupling agent is preferably 11 or less, more preferably 8.5 or less, and even more preferably 4.3 or less, relative to 1 unit of the silane coupling agent, from the viewpoint of carrying out step 1 in a powder state.

[0045] Examples of the catalyst that can be used in step 1 include acids (e.g., acetic acid, trifluoroacetic acid, etc.), bases (e.g., ammonia, triethylamine, diethylamine, etc.), transition metals (e.g., Ti, Ni, Sn, etc.), metals containing transition metals, etc. Among these, from the viewpoints of good dispersibility with inorganic particles and improving the graft density of polymer graft chains on the composite particle surface, bases are preferred, secondary amines and / or tertiary amines are more preferred, and tertiary amines are even more preferred.

[0046] The secondary amine is an ammonia having two hydrogen atoms substituted with a hydrocarbon group, and in the present invention, preferred examples thereof include dipropylamine, diisopropylamine, dibutylamine, etc. The tertiary amine is an ammonia having all hydrogen atoms substituted with a hydrocarbon group, and preferred examples thereof include diethylmethylamine, triethylamine, ethyldiisopropylamine, tripropylamine, tributylamine, etc.

[0047] In step 1, a catalyst may or may not be used. When a catalyst is used, the amount of the catalyst to be used may be the amount usually used in the field of the present invention. 2 From the viewpoint of surface modification efficiency of inorganic particles, the amount is preferably 0.1 mol or more, more preferably 0.5 mol or more, and even more preferably 1 mol or more, whereas from the viewpoint of suppressing reaction between silane compounds, the amount is preferably 1000 mol or less, more preferably 100 mol or less, and even more preferably 10 mol or less.

[0048] Furthermore, from the viewpoint of improving the graft density of polymer graft chains on the composite particle surface, the ratio ((A') / (B)) of the total mass of inorganic particles (A'[g]) to the total mass of substances that are liquid at 25°C and 1 atmospheric pressure (B[g]) among the components used in step 1 is preferably 2 or more, more preferably 3 or more, even more preferably 5 or more, and even more preferably 10 or more. On the other hand, from the viewpoint of the surface modification efficiency of the inorganic particles, (A') / (B) is preferably 100 or less, more preferably 80 or less, and even more preferably 60 or less. In addition, the total surface area of ​​inorganic particles (A[m 2 Regarding the relationship between (A') / (B) and (A') / (B), it is more preferable that the value of (A') / (B) is within the above-mentioned range and further satisfies log(A) ≧ −6.2log((A') / (B)) + 2.35, from the viewpoint of carrying out step 1 in a powder state.

[0049] After the reaction between the silane compound and the inorganic particles, unreacted components can be removed to obtain inorganic particles having polymerization initiation groups other than halosulfonyl groups bonded to their surfaces.

[0050] [Process 2] In step 2, the monomer is graft polymerized in the presence of inorganic particles to which polymerization initiation groups are bonded. Step 2 can be preferably carried out under known conditions for living radical polymerization. In this specification, "under living radical polymerization conditions" means that polymerization conditions appropriately selected by a person skilled in the art are adopted so that living radical polymerization starting from the polymerization initiation groups formed on the surfaces of inorganic particles to which polymerization initiation groups are bonded proceeds reliably and satisfactorily.

[0051] Examples of the monomer used in step 2 include styrene-based monomers, nitrile-based monomers, (meth)acrylic-based monomers, unsaturated olefins, conjugated diene-based monomers, and other monomers having specific groups in their side chains. Specific examples of the acrylate include butyl methacrylate, butyl acrylate, ethyl methacrylate, ethyl acrylate, methyl methacrylate, methyl acrylate, acrylamide, acrylonitrile, 4-benzoylphenyl acrylate, benzyl methacrylate, cyclohexyl methacrylate, N,N-dimethylmethacrylamide, dodecyl acrylate, dodecyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, glycidyl methacrylate, n-hexyl methacrylate, methacrylamide, methacrylic acid, acrylic acid, octadecyl acrylate, phenyl acrylate, propyl methacrylate, vinyl acetate, methoxypolyethylene glycol acrylate, methoxypolyalkylene glycol methacrylate, styrene, p-bromostyrene, 4-tert-butylstyrene, p-chlorostyrene, 4-iodostyrene, p-methoxystyrene, p-methylstyrene, sodium p-styrenesulfonate, and vinylbenzyl chloride.

[0052] The amount of monomer used in step 2 is determined based on the surface area of ​​the inorganic particles to which the polymerization initiation group is bonded (1 m2). 2 From the viewpoint of the efficiency of introducing the polymer, the amount of the monomer is preferably 0.00001 mol or more, more preferably 0.0001 mol or more, and even more preferably 0.001 mol or more, relative to the unit specific surface area of ​​the inorganic particles to which the polymerization initiating groups are bonded, while from the viewpoint of controlling the polymerization, the amount of the monomer is preferably 10 mol or less, more preferably 1 mol or less, and even more preferably 0.1 mol or less, relative to the unit specific surface area of ​​the inorganic particles to which the polymerization initiating groups are bonded.

[0053] The graft polymerization is carried out using a copper halide such as copper bromide or copper chloride as a catalyst. The ligand complex for the copper halide is not particularly limited, and examples thereof include tris(2-(dimethylamino)ethyl)amine, N,N,N'',N''-pentamethyldiethylenetriamine, 1,1,4,7,10,10-hexamethyltriethylenetetraamine, 1,4,8,11-tetramethyl-1,4,8,11-azacyclotetradecane, and bipyridine. The amount of copper halide as a catalyst is usually 0.1 to 1.0 part by mass based on 100 parts by mass of the monomer.

[0054] The solvent used in the polymerization is not particularly limited as long as it can dissolve the monomers, and examples thereof include anisole, toluene, tetrahydrofuran, acetonitrile, methanol, 2-propanol, hexane, octane, dodecane, and 2,2,2-trifluoroethanol.

[0055] The reaction temperature is usually 30 to 200°C, preferably 50 to 150°C. After the graft polymerization, it is preferable to remove unreacted monomers and free polymers that are not bonded to the inorganic particles by a known method.

[0056] <Resin composition and method for producing resin composition> The resin composition of the present invention contains the composite particles obtained by the above-mentioned production method and a resin. 〔resin〕 As the resin, a thermoplastic resin is preferred from the viewpoint of processability, and a thermosetting resin is preferred from the viewpoint of heat resistance. Examples of the thermoplastic resin include polyolefin resin, polyester resin, polyamide resin, ABS resin, polystyrene resin, polycarbonate resin, vinyl chloride resin, acrylic resin, etc. Among these, from the viewpoint of ease of handling of the obtained resin composition such as moldability, preferably one or more types selected from the group consisting of polyolefin resin, polyamide resin, and ABS resin, more preferably one or more types selected from the group consisting of polyolefin resin, and even more preferably polypropylene resin. The mass average molecular weight of the thermoplastic resin is not particularly limited, but may be from 5,000 to 500,000.

[0057] Examples of thermosetting resins include polyurethane resins, urea resins, phenolic resin foams, unsaturated polyester resins, alkyd resins, melamine resins, epoxy resins, silicon resins, and modified polyphenylene ether resins. Among these, modified polyphenylene ether resins are preferred from the viewpoint of exhibiting excellent low dielectric properties. Specific examples of modified polyphenylene ether resins include resins obtained by using modified polyphenylene ether compounds described in WO2019 / 065941 and crosslinking curing agents having carbon-carbon unsaturated double bonds in the molecule. The mass average molecular weight of the thermosetting resin is not particularly limited, but may be in the range of 100 to 500,000.

[0058] The amount of the resin in the resin composition of the present invention is preferably 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more from the viewpoint of moldability. On the other hand, from the viewpoint of function expression, it is preferably 95% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less. When two or more kinds of resins are blended, the amount is the total amount of each resin.

[0059] The amount of the composite particles in the resin composition of the present invention is preferably 1% by mass or more, more preferably 10% by mass or more, even more preferably 20% by mass or more, and even more preferably 25% by mass or more, from the viewpoint of functional expression. On the other hand, from the viewpoint of dispersibility of the composite particles in the resin, it is preferably 75% by mass or less, more preferably 60% by mass or less, even more preferably 55% by mass or less, and even more preferably 50% by mass or less. When two or more kinds of composite particles are contained, the amount is the total amount of each composite particle.

[0060] The resin composition of the present invention may contain, as components other than those described above, a chain extender, a plasticizer, an organic crystal nucleating agent, an inorganic crystal nucleating agent, a hydrolysis inhibitor, a flame retardant, an antioxidant, a lubricant such as a hydrocarbon wax or an anionic surfactant, an ultraviolet absorber, an antistatic agent, an antifogging agent, a light stabilizer, a pigment, an antifungal agent, an antibacterial agent, a foaming agent, other polymer materials, and the like.

[0061] [Method for producing resin composition] Such a resin composition of the present invention can be produced by a production method having a step of mixing the composite particles obtained by the above-mentioned production method with a resin. For example, a manufacturing method including a step of melt-kneading a resin and a composite particle can be mentioned. For melt-kneading, a known kneading machine such as an internal kneader, a single-screw or twin-screw extruder, or an open roll type kneader can be used. After melt-kneading, the melt-kneaded product may be dried or cooled according to a known method. In addition, the raw materials may be mixed uniformly in advance using a Henschel mixer, a super mixer, or the like, and then subjected to melt-kneading. The melt-kneading temperature and the melt-kneading time are not necessarily set depending on the type of raw materials used, but are preferably 170 to 240°C and 15 to 900 seconds.

[0062] In relation to the above-mentioned embodiment, the present invention further discloses the following method for producing composite particles, method for producing a resin composition, and resin composition. [1] A method for producing composite particles having polymer graft chains, comprising the following steps, in which step 1 is carried out in a powder state. (Step 1) A step of reacting inorganic particles with a silane compound having a polymerization initiating group other than a halosulfonyl group to bond the polymerization initiating group to the inorganic particles. (Step 2) A step of graft polymerizing a monomer in the presence of inorganic particles to which the polymerization initiation groups are bonded

[0063] [2] The manufacturing method according to [1], wherein the powder is a collection of particles, no liquid phase can be confirmed by visual observation, no caking occurs, and the powder has fluidity. [3] The manufacturing method described in [1] or [2], wherein the fluidity means that the material passes through a funnel (with a lower outlet diameter of 5 mm) without resistance and has an angle of repose of 25 degrees or more and 65 degrees or less. [4] Among the components used in step 1, the ratio of the total surface area of ​​inorganic particles (A [m 2 ]) ratio ((A) / (B)[m 2[1] to [3], wherein the molecular weight of the polymer is 20 or more and 1,000 or less. [5] The above (A) / (B) [m 2 / g] is 45 or more and 1,000 or less. [6] The above (A) / (B) [m 2 / g] is 50 or more and 700 or less. [7] The above (A) / (B) [m 2 / g] is 70 or more and 500 or less. [8] The method according to any one of [1] to [7], wherein the ratio ((A') / (B)) of the total mass of inorganic particles (A'[g]) to the total mass of liquid substances (B[g]) at 25°C and 1 atmosphere in the components used in step 1 is 2 or more and 100 or less. [9] The method according to any one of [1] to [8], wherein the (A') / (B) is 3 or more and 60 or less.

[10] The method according to any one of [1] to [9], wherein (A), (B), and (A') satisfy the following formula: log(A)≧-6.2log((A') / (B))+2.35

[11] The method according to any one of [1] to

[10] , wherein the inorganic particles have an average particle size of 1 nm or more and 100 μm or less.

[12] The method according to any one of [1] to

[11] , wherein the inorganic particles have an average particle size of 3 nm or more and 10 μm or less.

[13] The method according to any one of [1] to

[12] , wherein the inorganic particles have an average particle size of 50 nm or more and 1 μm or less.

[14] The method according to any one of [1] to

[13] , wherein the inorganic particles have an average particle size of 100 nm or more and 500 nm or less.

[15] The production method according to any one of [1] to

[14] , further comprising using a catalyst in step 1.

[16] The catalyst is triethylamine, and the amount of triethylamine added is 1 nm2 The method according to

[15] , wherein the amount of the compound is 0.1 moles or more and 1,000 moles or less relative to the amount of the compound.

[17] The method according to any one of [1] to

[16] , wherein in step 1, a solvent further containing an organic solvent and / or water is used.

[18] The production method according to

[17] , wherein the organic solvent includes one or more selected from ethanol, dichloromethane, toluene, acetone, tetrahydrofuran, methanol, butanol, and butyl cellosolve, preferably includes one or more selected from ethanol, toluene, tetrahydrofuran, and methanol, more preferably includes one or more selected from ethanol, toluene, and tetrahydrofuran, and even more preferably includes ethanol.

[19] The method according to

[17] or

[18] , wherein the content mass ratio of the organic solvent to the silane coupling agent is 0.1 or more and 10 or less, preferably 0.5 or more and 8 or less, more preferably 1 or more and 4 or less, and even more preferably 2 or more and 4 or less.

[20] The method according to

[17] , wherein the organic solvent is ethanol, and the mass ratio of the ethanol to the silane coupling agent is 0.1 or more and 10 or less, preferably 2 or more and 4 or less, relative to 1 of the silane coupling agent.

[21] The method according to any one of

[17] to

[20] , wherein the mass ratio of water to the silane coupling agent is 0.01 or more and 1 or less, preferably 0.05 or more and 0.5 or less, more preferably 0.1 or more and 0.3 or less, and even more preferably 0.2 or more and 0.3 or less.

[22] The method according to any one of

[17] to

[21] , wherein, when an organic solvent, alcohol, and water, are used in combination, the mass ratio of the alcohol and water to the silane coupling agent is 11 or less, preferably 8.5 or less, and more preferably 4.3 or less.

[23] The method according to any one of [1] to

[22] , wherein the amount of the silane compound having a polymerization initiating group other than a halosulfonyl group used relative to 100 parts by mass of inorganic particles is 0.1 parts by mass or more and 100 parts by mass or less, preferably 0.5 parts by mass or more and 50 parts by mass or less, and more preferably 1.0 parts by mass or more and 40 parts by mass or less.

[24] The production method according to any one of [1] to

[23] , comprising a step of contacting inorganic particles having a polymerization initiation group bonded thereto with a monomer under living radical polymerization conditions.

[25] The graft density of polymer chains on the surface of a composite particle is 0.001 chains / nm 2 More than 5 chains / nm 2 less than or equal to 0.01 chains / nm 2 More than 3 chains / nm 2 More preferably, it is 0.1 chains / nm or less. 2 More than 2 chains / nm 2 More preferably, it is 0.1 chains / nm or less. 2 More than 1 chain / nm 2 The method for producing a semiconductor device according to any one of [1] to

[24] ,

[26] A method for producing a resin composition, comprising a step of mixing the composite particles obtained by the production method according to any one of [1] to

[25] above with a resin.

[27] The manufacturing method according to

[26] , wherein the resin is a thermoplastic resin.

[28] The manufacturing method according to

[27] , wherein the thermoplastic resin is at least one selected from the group consisting of polyolefin resin, polyester resin, polyamide resin, ABS resin, polystyrene resin, polycarbonate resin, vinyl chloride resin, and acrylic resin.

[29] The method according to

[27] or

[28] , wherein the thermoplastic resin is a polypropylene resin having a mass average molecular weight of 5,000 or more and 500,000 or less.

[30] The manufacturing method described in

[26] , wherein the resin is a thermosetting resin.

[31] The manufacturing method according to

[30] , wherein the thermosetting resin is at least one selected from the group consisting of polyurethane resin, urea resin, phenolic resin foam, unsaturated polyester resin, alkyd resin, melamine resin, epoxy resin, silicone resin, and modified polyphenylene ether resin.

[32] The method according to

[30] , wherein the thermosetting resin is a modified polyphenylene ether resin.

[33] A method for producing composite particles having polymer graft chains, comprising the steps of: (a) carrying out step 1 in a powder state; and (b) providing composite particles obtained by the method for producing composite particles. resin A resin composition comprising: (Step 1) A step of reacting inorganic particles with a silane compound having a polymerization initiating group other than a halosulfonyl group to bond the polymerization initiating group to the inorganic particles. (Step 2) A step of graft polymerizing a monomer in the presence of inorganic particles to which the polymerization initiation groups are bonded

[34] A method for producing composite particles having polymer graft chains, comprising: step 1 of reacting inorganic particles with a silane compound having a polymerization initiating group other than a halosulfonyl group to bond the polymerization initiating group to the inorganic particles; and step 2 of graft polymerizing a monomer in the presence of the inorganic particles to which the polymerization initiating group is bonded, Among the components used in step 1, the ratio of the total surface area of ​​inorganic particles (A [m 2 ]) ratio ((A) / (B)[m 2 A resin composition comprising composite particles obtained by the method for producing composite particles, in which a molecular weight distribution (Mg / g) of the composite particles is 20 or more, and a resin.

[35] Composite particles having polymer graft chains obtained by a production method including step 1 of reacting inorganic particles with a silane compound having a polymerization initiating group other than a halosulfonyl group to bond the polymerization initiating group to the inorganic particles, and step 2 of graft polymerizing a monomer in the presence of the inorganic particles to which the polymerization initiating group is bonded, wherein the composite particles obtained by the production method include step 1, which is performed in a powder state.

[36] A resin composition comprising the composite particles according to

[35] above and a polypropylene resin having a mass average molecular weight of 5,000 or more and 500,000 or less.

[37] A resin composition comprising the composite particle according to

[35] above and a modified polyphenylene ether resin. EXAMPLES

[0064] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the following examples.

[0065] [Graft density of polymer chains on the surface of composite particles] Graft density of polymer chains on the surface of composite particles (chains / nm 2 ) is the mass per unit area of ​​the grafted chains attached to the surface of the composite particle (g / nm 2 ) and the number average molecular weight (Mn) of the grafted chains were measured, and the molecular weight was calculated using the following formula. Graft density (chains / nm 2 ) = [mass of grafted chains per unit area (g / nm 2 ) / number average molecular weight of grafted chains × (Avogadro's number)

[0066] Here, the mass of the grafted chains was determined by thermogravimetry (TG). More specifically, the composite particles to be measured were heated in air from 40°C to 500°C at a rate of 10°C / min, and the weight loss rate was measured. Furthermore, the "mass of the grafted chains per unit area" was calculated from the specific surface area of ​​the inorganic particles, which were the raw material of the composite particles to be measured. The number average molecular weight of the grafted chains was determined by gel permeation chromatography (GPC) as described below.

[0067] [Number average molecular weight of polymer graft chains in composite particles] The number average molecular weight of the polymer graft chains in the composite particles was measured by taking the number average molecular weight of the polymer chains that were not bonded to the composite particles and were produced simultaneously in the process of producing the composite particles as the number average molecular weight of the polymer graft chains. The number average molecular weight was measured by gel permeation chromatography (GPC) using a TSKgel GMHHR-H+GMHHR-H (cation) (manufactured by Tosoh Corporation) as a column, chloroform as a solvent, a flow rate of 1.0 mL / min, and a column temperature of 40° C., using polystyrene as a molecular weight standard.

[0068] [Method of measuring the specific surface area of ​​inorganic particles and calculating the total surface area] The specific surface area of ​​the inorganic particles was measured by the method of JIS Z 8833 (corresponding international standard: ISO 14488:2007). That is, the amount of adsorbed gas [cm] obtained by the gas adsorption method conforming to JIS Z 8830:2001 (corresponding international standard: ISO 9277:2010) for particle samples collected according to JIS Z 8833 3 The specific surface area of ​​the inorganic particles was calculated from the adsorption isotherm based on the so-called BET theory from [Amount of water absorbed by the inorganic particles per unit area / g]. In this specification, the value obtained by the static volume method using BELSORP-miniII manufactured by BELCO Japan was used. The total surface area was calculated as the product of the mass of the inorganic particles used and the specific surface area of ​​the inorganic particles.

[0069] [Glass transition temperature of polymer graft chains in composite particles] Measurement was performed according to the method of JIS K 7121. That is, the heat capacity was measured by heating the composite particles from 40° C. to 200° C. at a rate of 10° C. / min using a differential scanning calorimeter (DSC7020 manufactured by Hitachi High-Tech Science Corporation). The midpoint glass transition temperature Tmg (° C.) was determined as the temperature at the point where a straight line equidistant in the vertical direction from the extended straight line of each baseline intersected with the curve of the stepwise change portion of the glass transition in the DSC thermogram.

[0070] [Film thickness of polymer graft chains in composite particles] The film thickness was calculated from the following formula. The polymer density in the formula was determined as the polymer density of the polymer graft chains that were not bonded to the composite particles and were produced simultaneously in the process of producing the composite particles. The polymer density was measured by the pycnometer method in accordance with JIS K 7112.

[0071]

number

[0072] [Angle of repose of composite particles] The angle of repose of the composite particles was measured using a powder tester (PT-R, manufactured by Hosokawa Micron Corporation).

[0073] Synthesis Example 1 [Synthesis of silane compounds having polymerization initiating groups other than halosulfonyl groups] In a 500 mL eggplant flask, 17.9 g of 3-aminopropyltrimethoxysilane (KBM-903, Shin-Etsu Chemical Co., Ltd.), 100 mL of anhydrous tetrahydrofuran (THF), and 16.8 mL of anhydrous triethylamine (Tokyo Chemical Industry Co., Ltd.) were added. The mixture was cooled on ice, and when it reached 0°C, 14.8 mL of 2-bromoisobutyl bromide (BiBB) (Tokyo Chemical Industry Co., Ltd.) was added dropwise while maintaining the ice cooling, and the mixture was stirred for 4 hours. After that, the solvent was removed from the liquid phase obtained by filtration using an evaporator. The residue was dried at 50°C for 5 hours to obtain a silane compound having a bromoacyl group, which is a polymerization initiator group (this compound is abbreviated as "APTMS-Br"). This silane compound was used as a silane coupling agent. The synthesis scheme of the above-mentioned APTMS-Br is shown below.

[0074] [ka]

[0075] Example 1 [Process 1] Silica particles (Admatechs, SO-C2, average particle size 500 nm, specific surface area 5.5 m) were placed in a plastic bag. 2 50 g of 1000 g / g of PTMS-Br and 0.23 g of anhydrous triethylamine as a catalyst were added and mixed by hand from the outside of the bag at room temperature for 5 minutes. 0.74 g of APTMS-Br was added and mixed by hand from the outside of the bag at room temperature (approximately 25°C, the same applies below). These were mixed at room temperature for 5 minutes using a crush mill (manufactured by Iwatani Corporation) and then left to stand for 12 hours. The components that were liquid at 25°C and 1 atmospheric pressure in this step 1 were APTMS-Br and anhydrous triethylamine. Visual observation of the state of step 1 showed that the system was in a powder state throughout step 1. Thereafter, the silica microparticles were washed with ethanol, and subsequently, the silica microparticles were recovered by centrifugation, and then heated at 110° C. for 1 hour to obtain silica microparticles to which bromoacyl groups, which are polymerization initiator groups, were bonded.

[0076] [Process 2] 6 g of the above particles having polymerization initiator groups bonded thereto, 30 mL of anisole (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 90 g of the monomer butyl methacrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were placed in a 500 mL separable flask, heated to 80°C, thoroughly stirred, and then nitrogen bubbling was performed for 1 hour. Separately, 431 mg of Cu(I)Br (Tokyo Chemical Industry Co., Ltd.) and 1,040 mg of pentamethyldiethylenetriamine (Tokyo Chemical Industry Co., Ltd.) were stirred in 2 mL of anisole to prepare an anisole solution.

[0077] Next, the entire amount of this anisole solution was poured into the flask to initiate living radical polymerization, that is, stirring was continued at 80° C. for 10 minutes. The silica particles were then washed with methanol and the polybutyl methacrylate-grafted silica particles were collected by centrifugation. The graft density on the surface of the resulting silica particles was 0.30 chains / nm. 2 The number average molecular weight of the grafted chains was 33,000.

[0078] Example 2 [Process 1] Silica particles (Admatechs, SO-C2, average particle size 500 nm, specific surface area 5.5 m) were placed in a plastic bag. 2 50 g of 100% ethanol (1.0 g / g) and 0.23 g of anhydrous triethylamine were added and mixed by hand from the outside of the bag at room temperature for 5 minutes. 0.74 g of APTMS-Br and 0.74 g of ethanol were added and mixed by hand from the outside of the bag at room temperature for 5 minutes. Subsequently, silica fine particles having polymerization initiation groups bonded thereto were obtained by carrying out the same treatment as in Example 1. Although a small amount of ethanol was added as a solvent in this Example, the state of the system in step 1 was a powder state.

[0079] [Process 2] 6 g of the above particles having polymerization initiator groups bonded thereto, 30 mL of anisole (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 90 g of the monomer butyl methacrylate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were placed in a 500 mL separable flask, heated to 80°C, thoroughly stirred, and then nitrogen bubbling was performed for 1 hour. Next, the entire amount of the anisole solution was poured into the flask to initiate living radical polymerization in the same manner as in Example 1, thereby obtaining silica fine particles having graft chains of polymethacrylic acid.

[0080] Example 3 The silica particles were mixed with another silica particle (Admatechs, SO-C1, average particle size 200 nm, specific surface area 17.0 m 2 Silica fine particles having graft chains of polymethacrylic acid were obtained in the same manner as in Example 1, except that the amount of the silane coupling agent and catalyst was changed to the amounts shown in Table 1. Since no solvent was used in this Example, the state of the system in step 1 was a powder state.

[0081] Example 4 The silica particles were mixed with another silica particle (Degussa, Aerosil 200, average particle size 12 nm, specific surface area 200 m 2 Silica fine particles having graft chains of polymethacrylic acid were obtained in the same manner as in Example 1, except that the amount of the silane coupling agent and catalyst was changed to the amounts shown in Table 1. Since no solvent was used in this Example, the state of the system in step 1 was a powder state.

[0082] Example 5 Silica microparticles having graft chains of polymethacrylic acid were obtained in the same manner as in Example 2, except that the silane coupling agent was changed to another silane coupling agent having a bromoacyl group, which is a polymerization initiator group, bonded thereto (Tokyo Chemical Industry Co., Ltd., 2-bromo-2-methylpropanoate 3-(trimethoxysilyl)propyl (abbreviated as "PTMS-Br"), and the amounts of the silane coupling agent and catalyst were changed to those shown in Table 1. Since no solvent was used in this example, the system was in a powder state in step 1. The structure of PTMS-Br is shown below.

[0083] [ka]

[0084] Example 6 Silica microparticles having polymethacrylic acid graft chains were obtained in the same manner as in Example 2, except that the amount of ethanol used was changed to the amount shown in Table 1. In this example, a small amount of ethanol was added as a solvent, but the system in step 1 was in a powder state.

[0085] Example 7 The silica particles were mixed with another silica particle (Admatechs, SO-C1, average particle size 200 nm, specific surface area 17.0 m 2 Silica microparticles having graft chains of polymethacrylic acid were obtained in the same manner as in Example 2, except that the amount of ethanol was changed to 1 / g, the amounts of the silane coupling agent and catalyst were changed to those shown in Table 1, water was added in addition to ethanol as a solvent, and the amounts of the silane coupling agent and catalyst were changed to those shown in Table 1. In this example, trace amounts of ethanol and water were added as solvents, but the state of the system in step 1 was a powder state.

[0086] Comparative Example 1 Silica nanoparticles (Degussa, Aerosil 200, average particle size 12 nm, specific surface area 200 m 2 8.0 g of 2-(4-chlorosulfonylphenyl)ethyltrimethoxysilane (hereinafter abbreviated as "Ts-Cl") was added dropwise to the silica nanoparticles while stirring them. After the addition was completed, the mixture was reacted at 110°C for 24 hours while stirring. The flask was then depressurized to remove unreacted materials.

[0087] Thereafter, the mixture was dried under reduced pressure in a light-shielded room temperature environment to obtain silica particles having chlorosulfonyl groups, which are polymerization initiator groups. In this comparative example (corresponding to step 1 in the present invention), the state of the system in the step of obtaining inorganic particles having polymerization initiator groups bonded thereto was a powder state. Note that Ts-Cl is a type of silane coupling agent having a chlorosulfonyl group (-SO2Cl), which is a halosulfonyl group.

[0088] 2.0 g of silica particles with chlorosulfonyl groups introduced, 2.0 g of 4-vinylbenzyl chloride, 0.7 g of sparteine, and 0.1 g of copper bromide were placed in a three-neck flask, and the atmosphere in the flask was replaced with nitrogen. The mixture was reacted at 60°C for 24 hours while stirring. Tetrahydrofuran was added to the reaction product, centrifuged, and the supernatant was discarded. The resulting solid was dried under reduced pressure to obtain silica particles having polyvinylbenzyl chloride graft chains.

[0089] Reference example 1 Silica microparticles having polymethacrylic acid graft chains were obtained in the same manner as in Example 2, except that the amount of ethanol used as the solvent in step 1 was changed to 200 g. Since a solvent was used in this reference example, the system was in a liquid state in step 1.

[0090] Reference example 2 Silica microparticles having graft chains of polymethacrylic acid were obtained in the same manner as in Example 2, except that the amount of ethanol used as the solvent in step 1 was changed to 21.6 g. In this reference example, since a solvent was used, the state of the system in step 1 was a slurry. Therefore, the viscosity of the mixture was high, and it took a considerably longer time than in Example 2 to mix the entire mixture uniformly.

[0091] Example 8 Silica particles having polymethacrylic acid graft chains were obtained in the same manner as in Example 1, except that the amount of the silane coupling agent was changed to the amount shown in Table 3. Since no solvent was used in this example, the system in step 1 was in a powder state.

[0092] Example 9 Silica particles having graft chains of polymethacrylic acid were obtained in the same manner as in Example 3, except that the amount of the silane coupling agent was changed to the amount shown in Table 3. Since no solvent was used in this example, the system in step 1 was in a powder state.

[0093] Example 10 Silica microparticles having polystyrene graft chains were obtained in the same manner as in Example 6, except that the monomer was changed from butyl methacrylate to styrene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) In this example, a small amount of ethanol was added as a solvent, but the state of the system in step 1 was a powder state.

[0094] Example 11 Silica microparticles having polystyrene graft chains were obtained in the same manner as in Example 10, except that the mixing device in step 1 was changed from a crush miller to a super mixer (manufactured by Kawata Co., Ltd.). In this example, a small amount of ethanol was added as a solvent, but the state of the system in step 1 was a powder state.

[0095] Example 12 Silica particles are hollow silica (average particle size 1,900 nm, specific surface area 11.0 m 2 Hollow silica having polystyrene graft chains was obtained in the same manner as in Example 1, except that the amount of butyl methacrylate was changed to styrene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), the amount of silane coupling agent and the amount of catalyst were changed to those shown in Table 3. Since no solvent was used in this Example, the state of the system in step 1 was a powder state.

[0096] The hollow silica used in Example 12 was produced as follows. Emulsion A was obtained by mixing and stirring 388.6 g of ion-exchanged water, 200 g of dodecane (Kishida Chemical Co., Ltd.: primary n-dodecane), and 11.4 g of Coatamin 86W (Kao Corporation: containing 28% by mass of stearyl trimethylammonium chloride). A reaction tank was charged with 13,192.5 g of ion-exchanged water, 138.1 g of emulsion A, 125.6 g of Coatamin 24P (manufactured by Kao Corporation: containing 27.5% by mass of lauryl trimethylammonium chloride), and 3,120.8 g of ethyl orthosilicate (manufactured by Wacker Asahi Kasei Silicones: TEOS999), and the mixture was heated to 40°C with stirring, and then stirred for 10 minutes to obtain preparation solution B. Next, 221.5 g of AH212-CS (manufactured by Yokkaichi Chemical Co., Ltd.: containing 50% by mass of dimethylbis(2-hydroxyethyl)ammonium hydroxide) and 711.6 g of Cortamine 24P were mixed uniformly to obtain Preparation C. The entire amount of Preparation C was added to the entire amount of Preparation B at a constant rate, and then stirred at 40° C. for 3 hours to obtain a cloudy white liquid D. Next, the obtained cloudy liquid D was filtered using 5C filter paper (manufactured by Advantec Toyo Co., Ltd.), washed with water, and then dried at 110° C. to obtain white hollow silica particle precursors. The obtained hollow silica particle precursors were calcined at 1100° C. for 1 hour to obtain hollow silica.

[0097] The raw materials used in the above examples and the results are summarized in the table below. Note that the particles immediately after step 1 in Examples 1 to 12 all passed through a funnel (with a lower outlet diameter of 5 mm) without resistance.

[0098] [Table 1]

[0099] [Table 2]

[0100] [Table 3]

[0101] *The amount (parts by mass) of the silane coupling agent used per 100 parts by mass of inorganic particles. ** Angle of repose of particles immediately after step 1. *** Graft density of polymer chains on the surface of the obtained composite particles (chains / nm 2 ). The solvents ethanol, dichloromethane and water, the silane coupling agents APTMS-Br, PTMS-Br and Ts-Cl, and the catalyst triethylamine were all liquid components at 1 atmosphere.

[0102] In Comparative Example 1, composite particles were produced using the same inorganic particles as in Example 4, except that a silane compound having a chlorosulfonyl group was used as the polymerization initiator group. The graft density of the polymer graft chains on the surface of the obtained composite particles was 0.01 chains / nm 2 On the other hand, the graft density of the polymer graft chains on the surface of the inorganic composite particles produced in Example 4 was 0.18 chains / nm 2 This result suggests that the use of a silane compound having a halosulfonyl group as a polymerization initiator group reduces the graft density of the polymer graft chains on the surface of the obtained inorganic composite particles. The reason for this is presumably that the halosulfonyl group tends to generate radicals more frequently, causing the polymerization reaction to proceed too quickly, resulting in a reduction in the graft density.

[0103] Comparing Example 1 and Example 2, it was found that the graft density of the polymer graft chains on the surface of the obtained composite particles was higher in Example 2. This is believed to be because the presence of a good solvent for the silane coupling agent, such as ethanol, in step 1 improved the dispersibility of the silane coupling agent.

[0104] Comparing Example 3 and Example 7, it was found that Example 7, which contained a smaller amount of silane coupling agent, had a higher graft density of polymer graft chains on the surface of the obtained composite particles. This is believed to be due to the fact that the reactivity of the silane coupling agent was improved by the presence of water in addition to ethanol in step 1.

[0105] Reference Example 1 is an example in which the medium ethanol was used in excess of a prescribed amount during the synthesis of inorganic particles to which polymerization initiator groups were bonded. Comparing Reference Example 1 with Examples 1 and 2 in which the same type of silica fine particles were used, it was found that the graft density of the polymer graft chains on the surface of the inorganic composite particles produced in Reference Example 1 was smaller than that in Example 1 in which no medium was used and Example 2 in which a medium was used within the prescribed amount range.

[0106] Furthermore, it was found from Examples 10 to 11 that composite particles having polymer graft chains can be produced even when a monomer other than butyl methacrylate, for example, styrene, is used. [Industrial Applicability]

[0107] The composite particles obtained by the production method of the present invention can be used as a filler for a resin composition.

Claims

1. A method for producing composite particles having polymer graft chains, comprising the following steps, in which step 1 is carried out in a powder state. (Step 1) A step of reacting inorganic particles with a silane compound having a polymerization initiating group other than a halosulfonyl group to bond the polymerization initiating group to the inorganic particles. (Step 2) A step of graft polymerizing a monomer in the presence of inorganic particles having the polymerization initiation groups bonded thereto

2. Among the components used in step 1, the ratio of the total mass (B [g]) of liquid substances at 25° C. and 1 atmosphere to the total surface area (A [m 2 ]) ratio ((A) / (B) [m 2 2. The method according to claim 1, wherein the molecular weight of the polymer is 20 or more.

3. The method according to claim 1 or 2, wherein the ratio ((A') / (B)) of the total mass (A' [g]) of inorganic particles to the total mass (B [g]) of liquid substances at 25°C and 1 atmosphere among the components used in step 1 is 2 or more.

4. The method according to any one of claims 1 to 3, comprising a step of contacting inorganic particles having a polymerization initiation group bonded thereto with a monomer under living radical polymerization conditions.

5. The graft density of the polymer graft chains on the surface of the composite particle is 0.001 chains / nm 2 More than 5 chains / nm 2 The method according to any one of claims 1 to 4, wherein:

6. The method according to any one of claims 1 to 5, wherein the amount of the silane compound having a polymerization initiating group other than a halosulfonyl group used is 0.1 parts by mass or more and 100 parts by mass or less based on 100 parts by mass of the inorganic particles.

7. The process according to any one of claims 1 to 6, wherein the polymerization initiating group is an α-haloacyl group, a haloalkyl group, or a haloalkylphenyl group.

8. The method according to any one of claims 1 to 7, wherein in step 1, one or more selected from the group consisting of ethanol, dichloromethane, toluene, acetone, tetrahydrofuran, methanol, butanol, and butyl cellosolve are further used.

9. The method according to any one of claims 1 to 8, further comprising using a catalyst in step 1.

10. A method for producing a resin composition, comprising a step of mixing the composite particles obtained by the method according to any one of claims 1 to 9 with a resin.

11. A method for producing composite particles having polymer graft chains, comprising the steps of: resin A resin composition comprising: (Step 1) A step of reacting inorganic particles with a silane compound having a polymerization initiating group other than a halosulfonyl group to bond the polymerization initiating group to the inorganic particles. (Step 2) A step of graft polymerizing a monomer in the presence of inorganic particles having the polymerization initiation groups bonded thereto

Citation Information

Patent Citations

  • Manufacturing method of polymer-coated particle

    JP2005120365A

  • Method for manufacturing antibacterial agent

    JP2010018535A

  • Thermoplastic resin composition

    JP2020196877A